Catalytic liquefaction of human feces over Ni-Tm/TiO2 catalyst and the influence of operating conditions on products. (1st February 2018) - Wang, Wenjia; Yang, Lei; Yin, Zhaosen; Kong, Shengyan; Han, Wei; Zhang, Jinglai
Highlights: Catalytic liquefaction could convert 89.77% of human feces. The highest biocrude yield was 53.16% with Ni-Tm/TiO2 catalyst. Catalyst, temperautre and time significantly influenced the biocrude composition. The distribution of gaseous products at different HTL conditions were analyzed. Abstract: In this study, human feces were hydrothermal liquefied and converted into biocrude over Ni-Tm/TiO2 catalyst. The influence of catalysts, reaction temperature, and holding time on the distribution of products and element content of biocrude was assessed. The biocrude yield increased to 53.16% with a reaction temperature of 330 °C, a holding time of 30 min, and adding Ni-Tm/TiO2 catalyst while the liquefaction conversion peaked at 89.61%. The biocrude had an HHV of 36.64 MJ/kg and was similar to heavy crude oil. The biocrude is rich in fatty acid amides, esters, and oxygen-containing-only heteroatom-ring compounds as well as some nitrogen-containing heteroatom-ring compounds. The main gaseous products were CO2, CH4, and C2 H6 . Hydrothermal liquefaction over Ni-Tm/TiO2 catalyst could be a potential method to handle human excrement treatment and produce biofuel.